Peran sendawa terhadap regurgitasi pada bayi baru lahir: A scoping review - Khotimah, Diah Khusnul; Fitri, Siti Yuyun Rahayu; Rakhmawati, Windy (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Regurgitation in newborns is a common problem that is often complained of by parents and can affect the comfort and quality of life of the baby. One factor that is thought to play a role in preventing regurgitation is the practice of burping after breastfeeding. Although many studies have discussed breastfeeding techniques and preventing regurgitation, the role of burping has not been explored in depth. Purpose: To explore the role of belching on regurgitation in newborns. Method: The scoping review used three databases, namely CINAHL, PubMed, and Scopus and one search engine, Google Scholar. The keywords used in the search were